STIGMA? WHAT STIGMA? A Contribution to the Debate on the Effectiveness of IMF Lending - Beatrice D. Scheubel; Andrea Tafuro; Benjamin Vonessen (Center for Economic Studies and ifo Institute (CESifo), 2018)
There is a perception that IMF programmes are not catalytic and instead associated with large capital outflows, higher refinancing costs for sovereigns and adverse movements in stock markets. This has led to concerns that an expectation of adverse effects of IMF programmes may deter countries from asking for an IMF programme when they need one, a form of `IMF stigma'. We address these questions using monthly data by estimating how and to which extent adverse market reactions to a programme materialise and how past experience with adverse market reactions affects subsequent IMF programme participation. Our results, derived with a propensity score matching approach, indicate no role for `IMF stigma' stemming from the fear of adverse market movements.
Keywords: E02; F32; F33; F34; 330; capital flows; IMF conditionality; IMF recidivism; global financial safety net; Asian crisis; treasury bill rates